Application of the pseudovirus-based neutralization assay in the search for new antiviral drugs - Larisa I. Karpenko; Nadezhda B. Rudometova; Lily F. Nizolenko; Valery B. Loktev (Журнал микробиологии, эпидемиологии и иммунобиологии, 2025)
In recent years, significant progress has been made in the field of drug development, particularly due to the use of computer modeling methods. One of the key stages in the development of new antiviral drugs is testing the efficacy of promising candidates in in vitro experiments using target viruses. The application of new technologies for conducting primary screening with pseudotyped viruses simplifies research, increases its efficiency and ensures the biosafety of the conducted studies.